Transition from Paediatric to Adult Care in CAH: 20 Years of Experience at a Tertiary Referral Center - Kiewert, Cordula; Jedanowski, Julia; Hauffa, Berthold P.; Petersenn, Stephan; Mann, Klaus; Führer, Dagmar; Unger, Nicole (Hormone and Metabolic Research, 2024)
Transition medicine aims at the coordinated transfer of young patients with a chronic disease from paediatric to adult care. The present study reflects 20 years of experience in transitioning patients with congenital adrenal hyperplasia (CAH) in a single center setting. Our endocrine transition-clinic was established in 2002 and offers joint paediatric and adult consultations. Data were evaluated retrospectively from 2002 to 2005 and 2008 to present. Fifty-nine patients (29 males) were transferred. Median age was 18.4 years (17.6–23.6). Ninety percent of the patients presented with 21-hydroxlase-deficiency (21-OHD), 38 patients (23 m) with salt-wasting (sw), 7 (1 m) with simple-virilising (sv) and 8 (3 m) with the non-classic (nc) form. Rarer enzyme deficiencies were found in 6 cases: 17α-OHD (2 sisters), P450-oxidoreductase-deficiency (2 siblings), 3β-hydroxysteroid-dehydrogenase-deficiency (1 m) and 11β-OHD (1 female). Thirty-four patients (57.6%, 20 m) are presently still attending the adult clinic, 1 patient (1.7%, m) moved away and 24 (40.7%, 8 m) were lost to follow-up (13 sw-21-OHD, 6 sv-21-OHD, 5 nc-21-OHD). Thirty-seven patients (62.7%) attended the adult clinic for >2 years after transfer, 17 (28.8%) for >10 years. In the lost to follow-up group, median time of attendance was 16.3 months (0–195.2). Defining a successful transfer as two or more visits in the adult department after initial consultation in the transition clinic, transfer was efficient in 84.7% of the cases. A seamless transfer to adult care is essential for adolescents with CAH. It requires a continuous joint support during the transition period, remains challenging, and necessitates adequate funding.
Keywords: transition; congenital adrenal hyperplasia; single centre experience